What’s in Your File Drawer?: the Case of the Missing Null in Criminology and Criminal Justice - Crow, Matthew (Crime & delinquency, 2023)
Analysis of scholarship in the physical, biological, and social sciences has discovered that peer-reviewed journals publish a much larger proportion of articles with statistically significant findings compared to articles with null results. Publication bias in criminology and criminal justice (CCJ) has received very little attention, however. The current study is an exploratory analysis of research in leading CCJ journals across 2 years to determine the current state of null findings in contemporary CCJ scholarship. Our findings are consistent with studies in other disciplines; null results are rare in leading CCJ journals. We explore the context of our findings, outline the importance of examining publication bias to improve CCJ research and better inform policy, and discuss the limitations of our approach.